Daisy and the trouble with kittens - Gray, Kes; Parsons, Garry (Red Fox London, 2009)
Daisy is going on holiday! In an actual plane to actual Spain! It's so exciting! She's never seen a palm tree before, or eaten octopus, or played Zombie Mermaids, or made so many new friends! Trouble is, five of them are small and cute and furry!!!!